Smart Blind Stick Using Face Recognition - Prasad, Beksy Anna; Varghese, Athira Rachel; B, Roshan; George, Anish (International Journal of Computer Sciences and Engineering, 2020)
The smart walking stick helps blind people to do their work easily and comfortably. To normal stick, the detection of the obstacle is extremely difficult and normal stick isn’t efficient for visually impaired persons. Because the blind person doesn’t know what sort of things happening ahead of them. It’s difficult to manoeuvre here and there. Here we use a fresh stick which uses Machine Learning and Artificial Intelligence to guide blinds on their daily lives. It Consists of Integrated Sensors for measuring distance between a vehicle and the user, and informs the user whether they can able to cross the road so they won't have to rely on anyone to guide them. It also predicts or informs the obstacles ahead of the user, so it will help the user to understand whether there is steps or anything that causes the user fall down. This stick even has built-in Cameras and Headphone to recognize people who move towards the user, only the saved one will be recognized, new person are going to be informed to the user that ―A stranger is approaching".